TRANSFORMASI GEN ARABIDOPSIS ASYMETRIC LEAVES2 (AS2) PADA ANGGREK PHALAENOPSIS AMABILIS (L.) Blume DENGAN MEDIATOR AGROBAKTERIUM TUMEFACIENS - Vincentia Esti Windiastri; Endang Serniarti (Pusbindiklat - LIPI, 2009)
The Asymmetric leaves2 (AS2) gene is an important gene of a model plant, Arabidopsis thaliana, that involved in leaf development. To understand the molecular mechanism of leaf development in orchid, we transformed the AS2 gene into the Phalaenopsis amabilis orchid protocorms (developing orchid embryos). Agrobacterium tumefaciens LBA4404 that contained T-DNA with 355:: AS2 construct and pGreen vector were used for transformation. The-21-day-old protocorms that co-cultivated with Agrobacterium culture containing pG35S::AS2/LBA 4404 and pG35S/LBA4404 were maintained on 100 mg/1 kanamycin containing medium. The growing plants were selected as candidate of transformants. The putative transformants were analysed by PCR with a pair of AS2 gene specific primers (ORF15 F2 and ORF I 5 R2), that amplifying 600 by fragment of AS2 gene. The result showed that 79 plants out of 7966 protocorms transformant p35S: : AS2 and 64 plants out of 4622 protocorms transformant pG35S were kanamycin resistants, the efficiency of transformations were 0.99% and 1.38%, respectively. Phenotype characterization of the transformation showed that they produced various abnormal leaves shapes: oval (34.18%), wildtype-like (30.38%), rectangular (26.58%), lobed (3.80%), fused (2.53%) and trumpet (2.53%). These data indicate that abnormal shape of leaves might be due to the expressions of AS2 transgene in P amabilis.